Uptake of the Interim Canada Dental Benefit: an investigation of data from the first 18 months of the program - Goubran, Saif; Cruz de Jesus, Vivianne; Menon, Anil; Olatosi, Olubukola O.; Schroth, Robert J. (Frontiers in Oral Health, 2024)
IntroductionIn 2022, the Government of Canada introduced the Interim Canada Dental Benefit (CDB) to support Canadian families with children <12 years of age. This program operated from October 1, 2022, to June 30, 2024, with two application periods. The purpose of this study was to analyze data on applications accepted by the Canada Revenue Agency (CRA) during the first 18 months of the program.MethodsThis study used available data sourced from the CRA for applicants as of March 29, 2024, and assessed as of April 5, 2024. Data covered the entirety of the first period (October 1, 2022–June 30, 2023) of the Interim CDB and the first nine months of the second period (July 1, 2023–March 29, 2024). The rate of child participation was calculated using population data from Statistics Canada (2021).ResultsOver the first 18 months of the Interim CDB, a total of 410,920 applications were submitted and $403M distributed; $197M for 204,270 applications in period 1 and $175M for 173,160 applications in the first nine months of period 2. Overall, 321,000 children received the Interim CDB in period 1 and 282,130 children received the Interim CDB in the first nine months of period 2. A total of 91.8% of applicants had a net family income <$70,000, receiving the maximum benefit amount. The provinces with the highest rate of child participation were Manitoba (77.1/1,000 period 1; 74.9/1,000 period 2), Ontario (82.5/1,000 period 1; 72.2/1,000 period 2), Nova Scotia (73.4/1,000 period 1; 71.1/1,000 period 2), and Saskatchewan (72.3/1,000 period 1; 68.2/1,000 period 2). Overall, projections suggest that there will be an increase in the number of applications approved in period 2 compared to period 1.ConclusionsUptake in the first three quarters of period 2 remained consistent and in many instances, revealed higher rates of applications by parents for the Interim CDB. However, it is uncertain how much of the funds were directly used for dental care. Analyzing this data will aid in policy recommendation for enhancement of the Canadian Dental Care Program.